PENGARUH WORK LIFE BALANCE DAN MOTIVASI TERHADAP LOYALITAS KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PT SIMS JAYA KALTIM - Suyudi, Akhmad; Khan, Ryan Basith Fasih (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the effect of work life balance and work motivation on employee loyalty with job satisfaction as a mediating variable at PT SIMS Jaya Kaltim, involving all company employees with a sample of 194 respondents. Human resources (HR) have an important role in determining the progress of a company. Employee loyalty is one indicator of superior HR quality, which is influenced by work life balance, work motivation, and job satisfaction. The results showed that work life balance has a positive and significant effect on job satisfaction and employee loyalty. Work motivation also has a positive and significant influence on job satisfaction and loyalty. In addition, work life balance and work motivation are proven to influence employee loyalty through job satisfaction as a mediating variable. This research confirms that work-life balance, as well as the provision of appropriate work motivation, is very important in increasing employee satisfaction and loyalty, which in turn can support the progress of the company.